2016
DOI: 10.4236/fns.2016.71004
|View full text |Cite
|
Sign up to set email alerts
|

Coffee and Caffeine Intake among Students of the Brazilian Northeast

Abstract: The purpose of this study was to evaluate the pattern of intake of coffee and caffeine-containing food among students in a post-secondary institution in northeastern Brazil. We interviewed 498 students. Among these students, 72.3% (n = 360) reported to consume coffee, with a higher prevalence among women (68.3%) and students aged between 18 and 25 years (82.8%). The student's residence itself was the top location for taking coffee (90.6%) and the most widely used method of preparation was brewing coffee using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
5
0
2
Order By: Relevance
“…The prevalence of caffeine intake per day among students from six different universities in Bahrain was high (98%), with coffee as the main source of caffeine intake (76%) [ 20 ]. A similar study reported 72.3% coffee intake among Brazilian students with a higher prevalence among females (68.3%) [ 21 ]. Moreover, a study performed in United Arab Emirates (UAE) university students (male 30.1% and female 69.9%) showed a high prevalence (85.1%) of caffeinated energy drink consumption [ 22 ].…”
Section: Discussionmentioning
confidence: 98%
“…The prevalence of caffeine intake per day among students from six different universities in Bahrain was high (98%), with coffee as the main source of caffeine intake (76%) [ 20 ]. A similar study reported 72.3% coffee intake among Brazilian students with a higher prevalence among females (68.3%) [ 21 ]. Moreover, a study performed in United Arab Emirates (UAE) university students (male 30.1% and female 69.9%) showed a high prevalence (85.1%) of caffeinated energy drink consumption [ 22 ].…”
Section: Discussionmentioning
confidence: 98%
“…One of them was the study by Chang et al (2017) conducted with Taiwanese college students who observed a higher prevalence of caffeine-containing tea (95%) than coffee use (57%). In a Brazilian scenario, Penafort et al (2016) observed a high prevalence (72.3%) of caffeine use among college students but did not address its associated factors. However, in despite of the high prevalence, the present study showed a higher rate and great part of the use refers to the consumption of coffee and 'chimarrão' (a typical Brazilian drink based on Ilex paraguariensis (Bracesco, Sanchez, Contreras, Menini, & Gugliucci, 2011).…”
Section: Variablesmentioning
confidence: 97%
“…However, the extent of the issue on the use of caffeine and college, has not been well elucidated. Few articles address the use of caffeine in college populations (Chang et al, 2017;Penafort et al, 2016). One of them was the study by Chang et al (2017) conducted with Taiwanese college students who observed a higher prevalence of caffeine-containing tea (95%) than coffee use (57%).…”
Section: Variablesmentioning
confidence: 99%
“…Specifically, CGAs, abundant bioactive compounds in the green coffee beans, have a health-giving property through direct antioxidant activity, anti-inflammatory activity, and modulatory effects in cells by selectively acting on multiple cell signaling pathways [25]. Recent epidemiological and experimental results indicate that drinking coffee regularly helps to prevent several chronic diseases, such as cardiovascular disease, diabetes mellitus, cancer, Parkinson's disease, and inflammatory conditions [26].…”
Section: Introductionmentioning
confidence: 99%